Ethnobotanical study of herbal medicine in Ranggawulung Urban Forest, Subang District, West Java, Indonesia - LILY SURAYYA EKA PUTRI; DASUMIATI DASUMIATI; KRISTIYANTO KRISTIYANTO; MARDIANSYAH MARDIANSYAH; CHAIRUL MALIK; LAKSMANA PUTRA LEUVINADRIE; EKA ADHI MULYONO (Society for Indonesian Biodiversity, 2016)
Putri LSE, Dasumiati, Kristiyanto, Mardiansyah, Malik C, Leuvinadrie LP, Mulyono EA. Biodiversitas 17: 172-176. Ethnobotanical study is the first time study done in Subang District, West Java, Indonesia focused in the surrounding area of Ranggawulung Urban Forest (RUF). This study is related to plants diversity in Ranggawulung urban forest which is under the management of PT. Pertamina EP Field Subang, Indonesia. The purpose of the study was to investigate and collect information from local people on the use of medicinal plants in Subang District, West Java, Indonesia. The field study was conducted from OctoberNovember 2015 in Subang District through deep personal interview and questionnaire then all information were written and documented. Based on the diversity index of Shannon-Wiener, RUF was categorized in high diversity (H’=3.64). The total number of plant species in RUF was 1655 species belonging to 179 species from 101 families and only 32 species used for traditional medicines among local peoples. The highest frequency of plant parts used were leaves (47%) and fruit (17%) and followed with other parts of trunk, root, tuber, latex, bark and seed. The form of decoction was the most frequently prepared and administered orally. It indicates that Skeleton-Muscular System Disorder (SMSD) and Endocrinal Disorder (ED) had the highest use reports which came from 19 species of plants belonging to 3 families (Moraceae, Meliaceae, and Myrtaceae) to heal diseases including diabetes and back pain/rheumatism. It can be stated that higher index of diversity in RUF did not directly affect the use of plants for traditional medicine. Socialization of herbal medicine used among local people has to be improved as there are many species of plants are available to heal many diseases surrounding Subang District.